SPECIFIC FEATURES OF INDUSTRIAL DEVELOPMENT IN UZBEKISTAN - Olchinbayev Otabek Abdusamad ugli (Web of Journals Publishing, 2025)
This in the article our country industry network, it to oneself typical aspects, 2024 first half indicators and in the field there is problems, to them conclusion and offers given.
Keywords: Industry, production production, factory, raw material, component part, economic efficiency, labor engineering, metallurgy, mechanical engineering, chemistry industry, food industry, construction industry, medicine industry.